Bénard-Marangoni instability in sessile droplet evaporating at constant contact angle mode on heated substrate. (May 2019) - Zhu, Ji-Long; Shi, Wan-Yuan; Feng, Lin
Highlights: Quasi-steady state flower-like patterns of Bénard-Marangoni (BM) instabilities were observed in a droplet evaporating at CCA mode. BM cell is intrinsically circular-arc except for the straight connecting boundaries between cells. BM cell number decreases following a square function of the evaporating time. Abstract: Marangoni instabilities in a sessile droplet evaporating at constant contact angle mode on a heated substrate were investigated through a series of experiments. The quasi-steady state flower-like patterns of Bénard-Marangoni instabilities were observed, which uniformly distributed along the azimuthal direction of droplet. With the receding of triple line, the cell number of the Bénard-Marangoni convection decreases one by one following a square function of the evaporating time while the flower-like pattern maintains the quasi-steady state continuously. Different from the classical polygonal cells in flat liquid layer, the shape of cells in droplet is circular-arc. The critical Marangoni numbers for the incipience as well as those for the disappearance of the Bénard-Marangoni patterns were determined experimentally. Besides numerical simulations were conducted and the detailed characteristics of the Bénard-Marangoni instability patterns inside the droplet are explained thoroughly.